Digital Resilience as a Moderator in the Adoption of Digital Tools for Teaching Vocational Subjects in Nigerian Universities: A TAM Perspective - Auta, Mohammed; Paul-Mgbeafulike , Vivian Stella; Ikpeama, Frednora Uchenna; Ufondu, Chidiebere Christopher (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study explores the moderating role of digital resilience in the adoption of digital tools for teaching vocational subjects in Nigerian universities through the lens of Technology Acceptance Model (TAM). Data were collected from 173 lecturers teaching vocational subjects across six universities using a structured questionnaire. Structural equation modeling (SEM) was used to test the relationships among perceived usefulness (PU), perceived ease of use (PEOU), digital resilience (DR), and adoption intention (AI). Results indicate that PU and PEOU significantly predict AI; however, digital resilience moderates only the relationship between PEOU and AI but not between PU and AI. These findings highlight the importance of developing digital resilience to enhance technology adoption especially in educational settings. Implications for policy, practice, and future research are discussed, emphasizing the need for targeted interventions to support lecturers teaching vocational subjects in adopting digital tools for vocational education programmes.